The Information and Communication Technology Literacy Level of Sukoharjo’s Senior High School Students - Hieronymus Purwanta; Sutiyah; Herimanto; Musa Pelu; Isawati; Dadan Adi Kurniawan (Prodi Pendidikan Teknik Informatika Universitas Pendidikan Ganesha, 2023)
The Ministry of Education and Culture inaugurated the Independent Curriculum for primary to secondary education in the new school year 2022/2023. Therefore, this study aims to obtain an overview of the readiness of information and communication technology (ICT) literacy skills mastered by public high school students. Research samples were taken from nine public high schools in Sukoharjo Regency, which implemented the Independent Curriculum. The focus of the research is directed at obtaining an overview of how their ICT literacy skills. The method used is a survey compiled based on the idea of Helsper Schneider, Deursen, and Laar about indicators of digital skills for the younger generation. They divided ICT literacy indicators into information, literacy of computers, media, communication, visuals, and technology. The survey results show that public high school students in Sukoharjo Regency have high ICT literacy skills, 59% in the good category and 5% in excellent. They are ready to take part in teaching-learning processes using the Independent Curriculum.